Defining What, How, Why: Enriching Exploration for Self & Department - Trey Guinn (Academic Chairpersons Conference Proceedings, 2018)
Ever find that your colleagues are not “on the same page” or “do not see eye-to-eye” about a solution, much less its underlying problem? This can be frustrating and at times seem personal. Our discussion will focus on a method used to help individuals and teams identify problems/solutions and understand the motivations held by self and others that often challenge consensus.
Keywords: Conflict Resolution; Communication; Personal Development; Leadership; Understanding Self and Others